Dietary antioxidants and the aetiology of pancreatic cancer: a cohort study using data from food diaries and biomarkers. Issue 10 (23rd July 2012) - Banim, Paul J R; Luben, Robert; McTaggart, Alison; Welch, Ailsa; Wareham, Nicholas; Khaw, Kay-Tee; Hart, Andrew R
Abstract : Objective: To investigate whether the dietary antioxidants vitamins C and E, selenium and zinc decrease the risk of developing pancreatic cancer, for the first time using 7-day food diaries, the most accurate dietary methodology in prospective work. Design: 23 658 participants, aged 40–74 years, recruited into the EPIC-Norfolk Study completed 7-day food diaries which recorded foods, brands and portion sizes. Nutrient intakes were calculated in those later diagnosed with pancreatic cancer and in 3970 controls, using a computer program with information on 11 000 foods. Vitamin C was measured in serum samples. The HRs of developing pancreatic cancer were estimated across quartiles of intake and thresholds of the lowest quartile (Q1) against a summation of the three highest (Q2–4). Results: Within 10 years, 49 participants (55% men), developed pancreatic cancer. Those eating a combination of the highest three quartiles of all of vitamins C and E and selenium had a decreased risk (HR=0.33, 95% CI 0.13 to 0.84, p<0.05). There were threshold effects (Q2–4 vs Q1) for selenium (HR=0.49, 95% CI 0.26 to 0.93, p<0.05) and vitamin E (HR=0.57, 95% CI 0.29 to 1.09, p<0.10). The HRs of quartiles for antioxidants, apart from zinc, were <1, but not statistically significant. For vitamin C, there was an inverse association with serum measurements (HR trend=0.67, 95% CI 0.49 to 0.91, p=0.01), but the threshold effect from diaries was not significant (HR=0.68, 95% CI 0.37 to 1.26). Conclusion: The results support measuring antioxidants in studies investigating the aetiology of pancreatic cancer. If the association is causal, 1 in 12 cancers might be prevented by avoiding the lowest intakes.